2022
DOI: 10.3390/jcm11195850
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Cerebral Ischemia after Aneurysmal Subarachnoid Hemorrhage: The Results of Induced Hypertension Only after the IMCVS Trial—A Prospective Cohort Study

Abstract: Delayed cerebral ischemia (DCI) is a predictor of poor outcome after aneurysmal subarachnoid hemorrhage (SAH). Treatment strategies vary and include induced hypertension and invasive endovascular treatment. After the IMCVS trial (NCT01400360), which failed to demonstrate a benefit of endovascular treatment for cerebral vasospasm (CVS) and resulted in a significantly worse outcome, we changed our treatment policy in patients with diagnosed CVS to induced hypertension only, and we present our prospective results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…We therefore changed our treatment policy in patients with diagnosed CVS to induced hypertension only and published our prospective results in the subgroup of SAH patients meeting inclusion criteria of the IMCVS trial recently [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore changed our treatment policy in patients with diagnosed CVS to induced hypertension only and published our prospective results in the subgroup of SAH patients meeting inclusion criteria of the IMCVS trial recently [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that commensal gut microbiota protects against ischemic stroke pathology and that their depletion leads to increased mortality and poor outcome, including worse neurological function (Singh et al, 2016;Winek et al, 2016). These findings become relevant given that SAH is a type of hemorrhagic stroke and has also been shown to cause delayed ischemic stroke (Martin and Rymer, 2011;Guresir et al, 2022). Compared to ischemic stroke not secondary to SAH, less is known about the association between SAH and the gut microbiome.…”
Section: A Role For the Microbiota-gut-brain Axis In Cerebrovascular ...mentioning
confidence: 99%
“…Cerebral ischemia is a common complication after SAH, with >30% of patients experiencing delayed cerebral ischemia ( Stienen et al, 2014 ). Decreased cerebral hypoperfusion leads to cerebral ischemia and cerebral infarction, ultimately inducing severe neurological dysfunction, brain injury and even death ( Güresir et al, 2022 ; Hostettler et al, 2022 ). Cerebral ischemia is caused by various factors, including cerebral vasospasm, micro thrombosis, blood-brain barrier destruction, inflammatory reactions and cerebral vascular self-regulation dysfunction ( Macdonald, 2014 ).…”
Section: Neuronal Necrosismentioning
confidence: 99%